El empleo de imágenes Landsat TM para la detección y cartografía de áreas incendiadas en el Prepirineo occidental oscense - Pérez Cabello, Fernando; De la Riva Fernández, Juan (Geographicalia, 2017)
A methodology for deteccion of surfaces affected by forest fires by using Landsat TM images is shown in this paper. The site of the study is based in the western Pyrennes of Huesca (Aragón) where often ocurr. The use of this kind of information can help in detecting damages caused by these events suporting traditional methods.
Keywords: Forest fire; Remote Censing; Landsat TM; Normalized Difference Vegetation Index (NDVI).